2017
DOI: 10.1016/j.jid.2017.02.986
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cells (MSCs) Attenuate Cutaneous Sclerodermatous Graft-Versus-Host Disease (Scl-GVHD) through Inhibition of Immune Cell Infiltration in a Mouse Model

Abstract: Human chronic graft-versus-host disease (GVHD) shares clinical characteristics with a murine sclerodermatous GVHD model that is characterized by skin thickening and lung fibrosis. A B10.D2 → BALB/c transplant model of sclerodermatous GVHD was used to address the therapeutic effect of mesenchymal stem cells (MSCs) on the development of chronic GVHD. The clinical and pathological severity of cutaneous sclerodermatous GVHD was significantly attenuated in MSC-treated recipients relative to sclerodermatous GVHD con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 47 publications
1
29
1
Order By: Relevance
“…Moreover, they demonstrated that BM-MSCs recruited T-cells for FASL-mediated apoptosis through the secretion of Monocyte Chemotactic Protein 1 (MCP-1) ( 47 ). Another study also demonstrates that allogeneic MSCs could attenuate a mice model of cutaneous sclerodermatous GVHD by selectively blocking immune cell migration and down-regulating chemokines and chemokine receptors ( 48 ).…”
Section: Rational Of Msc-based Therapy Of Sscmentioning
confidence: 99%
“…Moreover, they demonstrated that BM-MSCs recruited T-cells for FASL-mediated apoptosis through the secretion of Monocyte Chemotactic Protein 1 (MCP-1) ( 47 ). Another study also demonstrates that allogeneic MSCs could attenuate a mice model of cutaneous sclerodermatous GVHD by selectively blocking immune cell migration and down-regulating chemokines and chemokine receptors ( 48 ).…”
Section: Rational Of Msc-based Therapy Of Sscmentioning
confidence: 99%
“…In this murine Scl-GVHD model (34), infiltration of mononuclear cells (predominantly CD4 T cells and CD11b monocyte/macrophages) into target organs starts 14 days after allo-HSCT (8,11,35). After injection of hMSCs, the infiltration of mononuclear cells was profoundly reduced into the skin, whereas in the lungs, an increase in infiltrating CD4 T cells followed the early accumulation of CD11b cells.…”
Section: Discussionmentioning
confidence: 99%
“…The entry of leukocytes into lymphoid and nonlymphoid tissues is controlled by sequential engagement of inflammatory cytokines and/or chemokines (36,37). It has been previously shown that mMSCs attenuate cutaneous Scl-GVHD by selectively blocking immune cell migration and down-regulating chemokines and chemokine receptors (11). We wondered whether chemokine expression pattern was a factor determining the preferential organ involvement after early injection of hMSCs, which led us to analyze chemokine receptors involved in lung diseases (38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical characteristics of human chronic graft-versus-host disease (cGVHD) are similar to that of murine sclerodermatous GVHD model such as skin hyperkeratosis and pulmonary fibrosis. Lim et al indicated that MSCs were correlated with the remission of cutaneous sclerodermatous GVHD, whose potential mechanism might be down-regulating the migration of immune cells and eliminating the secretion of chemokines [96]. Research on MSCs applied in chronic anti-graft host disease (cGVHD) started rather late and is far from enough, which requires further research.…”
Section: Application In Chronic Graft-versus-host Disease (Cgvhd)mentioning
confidence: 99%